2012
DOI: 10.1039/c2jm16645c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterisation of oxyanion-doped manganites for potential application as SOFC cathodes

Abstract: In this paper we report the successful incorporation of borate and phosphate into CaMnO 3 and borate into La 1Ày Sr y MnO 3Àd . For CaMnO 3 , an increase in the electronic conductivity was observed, which can be correlated with electron doping due to the oxyanion doping favoring the introduction of oxide ion vacancies (as well as the higher valence of P 5+ compared to Mn 4+ in the case of phosphate doping). The highest conductivity at 800 C was observed for CaMn 0.95 P 0.05 O 3Àd , 43.0 S cm À1 , in comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 28 publications
1
36
0
1
Order By: Relevance
“…Most substitution attempts have focused on the use of metal cations with a similar size to that of Mn. In a departure from this trend, the Slater group devised a doping approach that used non‐metal cations, such as B and P as a substitute for Mn in CaMnO 3 (CMO), which also resulted in improved electrical conductivity and ORR performance in the SOFC (relative to that of CMO) . Incorporation of such dopants (i.e., B, P, Si, and S) can indeed stabilise the perovskite lattice effectively…”
Section: Introductionmentioning
confidence: 99%
“…Most substitution attempts have focused on the use of metal cations with a similar size to that of Mn. In a departure from this trend, the Slater group devised a doping approach that used non‐metal cations, such as B and P as a substitute for Mn in CaMnO 3 (CMO), which also resulted in improved electrical conductivity and ORR performance in the SOFC (relative to that of CMO) . Incorporation of such dopants (i.e., B, P, Si, and S) can indeed stabilise the perovskite lattice effectively…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many "cobalt-free" cathode materials are reported, which show high compatibility with other cell components and good long term stability as well as favorable electrochemical performance [28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, substituting La/Ba with an alkaline‐earth element (e.g., Sr or Ca) at the A‐site increased the electrical conductivity . However, it was recently reported that the B‐site doping in perovskite oxide by nonmetal elements such as boron (B) and phosphorus (P) also enhanced the conductivity . For example, Li et al demonstrated that the P doping increased the conductivity of SrCo 0.8 Fe 0.2 O 3− δ perovskite and thus enhanced the performance as an SOFC cathode at elevated temperatures .…”
Section: Introductionmentioning
confidence: 99%